2024
DOI: 10.1007/s11701-024-01954-2
|View full text |Cite
|
Sign up to set email alerts
|

Robotic assisted versus laparoscopic surgery for deep endometriosis: a meta-analysis of current evidence

Matteo Pavone,
Alessandro Baroni,
Federica Campolo
et al.

Abstract: Endometriosis is a benign inflammatory onco-mimetic disease affecting 10–15% of women in the world. When it is refractory to medical treatments, surgery may be required. Usually, laparoscopy is the preferred approach, but robotic surgery has gained popularity in the last 15 years. This study aims to evaluate the safety and efficacy of robotic-assisted laparoscopic surgery (RAS) versus conventional laparoscopic surgery (LPS) in the treatment of endometriosis. This study adheres to PRISMA guidelines and is regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It has been shown that operative time decreases in relation to the increase in surgeries performed [ 37 ], as well as the condition of the patients and the severity of endometriosis [ 24 , 26 , 31 ], as mentioned before. Further prospective studies comparing laparoscopy to the new robotic systems are needed to address the controversial results that have been reported [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that operative time decreases in relation to the increase in surgeries performed [ 37 ], as well as the condition of the patients and the severity of endometriosis [ 24 , 26 , 31 ], as mentioned before. Further prospective studies comparing laparoscopy to the new robotic systems are needed to address the controversial results that have been reported [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%